Isolation of dihydroflavonol 4-reductase cDNA clones from Angelonia x angustifolia and heterologous expression as GST fusion protein in Escherichia coli. - Christian Gosch; Karthik Mudigere Nagesh; Jana Thill; Silvija Miosic; Sylvia Plaschil; Malvina Milosevic; Klaus Olbricht; Shaghef Ejaz; Annette Rompel; Karl Stich; Heidi Halbwirth (PLoS ONE)
Blue Angelonia × angustifolia flowers can show spontaneous mutations resulting in white/blue and white flower colourations. In such a white line, a loss of dihydroflavonol 4-reductase (DFR) activity was observed whereas chalcone synthase and flavanone 3-hydroxylase activity remained unchanged. Thus, cloning and characterization of a DFR of Angelonia flowers was carried out for the first time. Two full length DFR cDNA clones, Ang.DFR1 and Ang.DFR2, were obtained from a diploid chimeral white/blue Angelonia × angustifolia which demonstrated a 99% identity in their translated amino acid sequence. In comparison to Ang.DFR2, Ang.DFR1 was shown to contain an extra proline in a proline-rich region at the N-terminus along with two exchanges at the amino acids 12 and 26 in the translated amino acid sequence. The recombinant Ang.DFR2 obtained by heterologous expression in yeast was functionally active catalyzing the NADPH dependent reduction of dihydroquercetin (DHQ) and dihydromyricetin (DHM) to leucocyanidin and leucomyricetin, respectively. Dihydrokaempferol (DHK) in contrast was not accepted as a substrate despite the presence of asparagine in a position assumed to determine DHK acceptance. We show that substrate acceptance testing of DFRs provides biased results for DHM conversion if products are extracted with ethyl acetate. Recombinant Ang.DFR1 was inactive and functional activity could only be restored via exchanges of the amino acids in position 12 and 26 as well as the deletion of the extra proline. E. coli transformation of the pGEX-6P-1 vector harbouring the Ang.DFR2 and heterologous expression in E. coli resulted in functionally active enzymes before and after GST tag removal. Both the GST fusion protein and purified DFR minus the GST tag could be stored at -80°C for several months without loss of enzyme activity and demonstrated identical substrate specificity as the recombinant enzyme obtained from heterologous expression in yeast.